Evaluation of the collaboration process from an individual and collaborative perspective - Coto, Mayela (2014)
Many proposals to evaluate the collaborative process focus on "measure" the group's participation in the fulfillment of the activity and do not consider the individual aspect. This paper reports the results of an exploratory study which aims to analyze the potential of the Google Drive (GD) tool for assessment of collaborative work process from an individual and collaborative perspective.